Wild Florida mottled ducks demonstrate strong heterogeneity in their humoral innate immune response - Andrea J. Ayala; Matthew Cheng; Thomas A. Hellinger; K. Mark McBride; Jonathan Webb; Andrew Fanning; Paul Snyder; Margherita Ferragamo; Samantha C. Garcia; Nyah Sterner; Karyn L. Bischoff; Salvador Almagro-Moreno; et al. (PLoS ONE, 2025)
The Florida Mottled Duck ( Anas fulvigula fulvigula ) is a unique subspecies of waterfowl whose range is limited to peninsular Florida, USA. As an endemic subspecies, Florida Mottled Ducks face numerous conservation stressors, such as habitat conversion and hybridization with non-native Mallards ( Anas platyrhynchos ). In addition to these numerous stressors, Mottled Ducks are also contending with emerging and/or geographically expanding waterborne pathogens such as Vibrio spp., due to the effects of climate change. However, even given their conservation needs, little is known with respect to the health, physiology, and the immunity of wild Mottled Ducks in Florida. Given this lack of data, we performed health assessments of Mottled Ducks in the Central Florida area. Specifically, we examined the humoral innate immune system, i.e., the plasma of Mottled Ducks in response to a common but extraneous pathogen: Escherichia coli strain American Type Culture Collection (ATCC) number 8739. We utilized a bactericidal assay (“bacterial killing assay” or BKA) commonly used in eco-immunology, to provide insight into the bactericidal capacities of captured Florida Mottled Ducks. We statistically tested the BKA capacity, or microbial killing ability, of 23 Mottled Ducks in response to age and whole blood lead levels (Pb). We found that there was no statistically significant relationship between the covariates we measured and Mottled Duck BKA capacity against E. coli . However, the variability we observed in the BKA capacity of this subspecies warrants further research into additional physiological and ecological covariates coupled with potential immune stressors that Florida Mottled Ducks may be contending with.